High-Mobility Group Box 1-Induced Complement Activation Causes Sterile Inflammation - Kim, Sook Young; Son, Myoungsun; Lee, Sang Eun; Park, In Ho; Kwak, Man Sup; Han, Myeonggil; Lee, Hyun Sook; Kim, Eun Sook; Kim, Jae-Young; Lee, Jong Eun; Choi, Ji Eun; Diamond, Betty; et al. (Frontiers in Immunology, 2018)
High mobility group box 1 (HMGB1), a well-known danger-associated molecular pattern (DAMP) molecule, acts as a pro-inflammatory molecule when secreted by activated immune cells or released after necrotic cell damage. HMGB1 binds to immunogenic bacterial components and augments septic inflammation. In this study, we show how HMGB1 mediates complement activation and promotes sterile inflammation. We show that HMGB1 activates the classical pathway of complement system in an antibody-independent manner after binding to C1q. The C3a complement activation product in human plasma and C5b-9 membrane attack complexes on cell membrane surface are detected after addition of HMGB1. In an acetaminophen (APAP)-induced hepatotoxicity model, APAP injection reduced HMGB1 levels and elevated C3 levels in C1q-deficient mouse serum samples, compared to that in wild-type (WT) mice. APAP-induced C3 consumption was inhibited by sRAGE treatment in WT mice. Moreover, in a mouse model of brain ischemia-reperfusion injury based on middle cerebral arterial occlusion C5b-9 complexes were deposited on vessels where HMGB1 was accumulated, an effect that was suppressed upon HMGB1 neutralization. We propose that the HMGB1 released after cell necrosis and in ischemic condition can trigger the classical pathway of complement activation to exacerbate sterile inflammation.